How do you simplify \frac { 3a } { 2a b } - \frac { 2a } { 4}3a2ab2a4?

1 Answer

(a(3 - ab))/(2b)a(3ab)2b

Explanation:

First, you make a common denominator.

(3a)/(2ab) - (2a)/4 = (3a)/(2ab) - (2*a^2*b)/(4ab)3a2ab2a4=3a2ab2a2b4ab

Next, you multiply the fraction (3a)/(2ab)3a2ab in the numerator and denominator by 22. Then you get

(6a)/(4ab)6a4ab

Now you do

(6a)/(4ab) - (2 * a^2 * b)/(4ab) = (2a(3-ab))/(4b) = (a(3 - ab))/(2b)6a4ab2a2b4ab=2a(3ab)4b=a(3ab)2b

Sorry for making it so complicated.